High Sensitivity Method to Estimate Distribution of Hyaluronan Molecular Sizes in Small Biological Samples Using Gas-Phase Electrophoretic Mobility Molecular Analysis. (10th September 2015) - Do, Lan; Dahl, Christen P.; Kerje, Susanne; Hansell, Peter; Mörner, Stellan; Lindqvist, Ulla; Engström-Laurent, Anna; Larsson, Göran; Hellman, Urban
Abstract : Hyaluronan is a negatively charged polydisperse polysaccharide where both its size and tissue concentration play an important role in many physiological and pathological processes. The various functions of hyaluronan depend on its molecular size. Up to now, it has been difficult to study the role of hyaluronan in diseases with pathological changes in the extracellular matrix where availability is low or tissue samples are small. Difficulty to obtain large enough biopsies from human diseased tissue or tissue from animal models has also restricted the study of hyaluronan. In this paper, we demonstrate that gas-phase electrophoretic molecular mobility analyzer (GEMMA) can be used to estimate the distribution of hyaluronan molecular sizes in biological samples with a limited amount of hyaluronan. The low detection level of the GEMMA method allows for estimation of hyaluronan molecular sizes from different parts of small organs. Hence, the GEMMA method opens opportunity to attain a profile over the distribution of hyaluronan molecular sizes and estimate changes caused by disease or experimental conditions that has not been possible to obtain before.